1992
DOI: 10.1126/science.1318579
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b 558 : the Flavin-Binding Component of the Phagocyte NADPH Oxidase

Abstract: The phagocyte respiratory burst oxidase is a flavin-adenine dinucleotide (FAD)-dependent dehydrogenase and an electron transferase that reduces molecular oxygen to superoxide anion, a precursor of microbicidal oxidants. Several proteins required for assembly of the oxidase have been characterized, but the identity of its flavin-binding component has been unclear. Oxidase activity was reconstituted in vitro with only the purified oxidase proteins p47phox, p67phox, Rac-related guanine nucleotide (GTP)-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
229
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(240 citation statements)
references
References 45 publications
9
229
0
2
Order By: Relevance
“…Evidence was presented that mitogen-acti/ated protein kinases could be involved in the activation of tl~e respiratory burst by FMLP [20][21][22]. However, the finding t}at the activation of the respiratory burst by PMA or ConA is not accompanied by tyrosine phosphorylation and transloc;Ltion of p125 GAP and the previous reports that the in vitro r, constitution of active NADPH oxidase does not require p ~25 GAP [34,35] are in contrast with this hypothesis. Therefire, the role of p125 GAP in the mechanisms of NADPH o ddase activation remains to be clarified.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence was presented that mitogen-acti/ated protein kinases could be involved in the activation of tl~e respiratory burst by FMLP [20][21][22]. However, the finding t}at the activation of the respiratory burst by PMA or ConA is not accompanied by tyrosine phosphorylation and transloc;Ltion of p125 GAP and the previous reports that the in vitro r, constitution of active NADPH oxidase does not require p ~25 GAP [34,35] are in contrast with this hypothesis. Therefire, the role of p125 GAP in the mechanisms of NADPH o ddase activation remains to be clarified.…”
Section: Discussionmentioning
confidence: 95%
“…Homology studies suggested that the 504 GLKQKTLYGR 513 region of gp91 phox may be important for binding of NADPH (34). This region, which slightly overlaps the epitope bound by mAb NL7, could be sequestered by bound Ab, thus obstructing the access of NADPH to gp91 phox .…”
Section: Examination Of Potential Changes In Nadph Binding On Gp91 Phmentioning
confidence: 99%
“…The two subunits, gp91-phox and p22-phox, are present at a 1:1 molar ratio [26] and are responsible for coordinating at least two hemes, one that may be shared between gp91-phox and p22-phox [27]. In addition, FAD and NADPH binding activities have been shown for gp91-phox [28,29]. Previous studies have shown that both gp91-phox and p22-phox are necessary for functional surface expression of the flavocytochrome b assembly, and a defect in one of the subunit proteins results in decreased expression of the other subunit [30].…”
Section: Introductionmentioning
confidence: 99%